Thomas Aquinas, the Beatific Vision and the Role of Christ: A Reply to Hans Boersma - Simon Francis Gaine (TheoLogica, 2018)
This article continues a conversation with Hans Boersma on the role of Jesus Christ in the beatific vision enjoyed by the saints. In his book Seeing God, Boersma maintained that there is a Christological deficit in Thomas Aquinas’s account of the beatific vision. In response I suggested that Aquinas held that Christ’s beatific vision is forever the cause of that of the saints. In his reply to me, Boersma more or less accepted my conclusion, but claimed there was still a Christological deficit because Aquinas mentions the thesis only rarely. He then drew attention to a second, more important factor in the alleged deficit, namely, Aquinas’s identification of the divine essence rather than Christ as the vision’s object. The present article responds to both elements of the alleged deficit, arguing against Boersma on the basis of the Summa Theologiae’s structure that there is no such deficit in Aquinas. While Boersma, after finding against Aquinas, moves in conclusion “towards a theophanic view of the beatific vision,” in my own conclusion I sketch out an alternative, Thomist account of the relationship between the beatific vision and heavenly theophany.